MIGRATION MOVEMENTS AND THEIR SCIENTIFIC ANALYSIS - Malахat SAIPOVА (TADQIQOTLAR, 2025)
Abstract: This article discusses about the movement of people around the world, focusing on migration movement, which is characterized by extreme diversity. It analyzes the scientific views of scientists regarding the reasons motivating migration, psychological characteristics of a person and given authors conclusion.